2019
DOI: 10.1038/s41598-019-45409-3
|View full text |Cite
|
Sign up to set email alerts
|

Complementing conventional infectious disease surveillance with national health insurance claims data in the Republic of Korea

Abstract: Surveillance remains an important tool for timely outbreak detection and response. Many countries, including Korea, have established national infectious disease surveillance systems with clinical notification. We aimed to evaluate the National Health Insurance Claims-based Surveillance (NHICS) compared to conventional passive report-based National Infectious Diseases Surveillance (NIDS). Reported to claimed cases ratios (R/C ratio) were evaluated from monthly notifiable disease cases captured by NIDS and NHICS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Since the reporting criteria for pertussis include suspected cases, the sharp increase starting from the 2013-2015 calendar year reflects the situation of South Korea in 2015 regarding the MERS outbreak. The effect of the MERS outbreak on reporting behavior has also been described in previous E p u b a h e a d o f p r i n t research, in which an interrupted time series analysis results showed an increase in the overall report of notifiable diseases, since the MERS outbreak [39].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since the reporting criteria for pertussis include suspected cases, the sharp increase starting from the 2013-2015 calendar year reflects the situation of South Korea in 2015 regarding the MERS outbreak. The effect of the MERS outbreak on reporting behavior has also been described in previous E p u b a h e a d o f p r i n t research, in which an interrupted time series analysis results showed an increase in the overall report of notifiable diseases, since the MERS outbreak [39].…”
Section: Discussionsupporting
confidence: 74%
“…According to a previous study that calculated the reporting and claim ratio (R/C ratio) of infectious diseases in South Korea, none of the VPDs showed an R/C ratio close to 1, neither did it exceed 0.5 [39]. Second, these data do not provide information about vaccination history, indicating that the study results simply assumed the effect of vaccination.…”
Section: Discussionmentioning
confidence: 78%
“…The HIRA claim database includes 46 million patients per year, approximately 90% of the total population in Korea, from almost 80,000 healthcare service provides 8 . The HIRA dataset comprises all insurance benefit claims by medical service providers and includes general sociodemographic information, diagnoses according to the 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10), the medical institution, medications prescribed, medical costs and survival status 9 . The HIRA shared nationwide data on 7590 patients infected with COVID-19 between January 20 (date of the first confirmed case) and May 27, 2020, with researchers in South Korea.…”
Section: Methodsmentioning
confidence: 99%
“…The outbreak and spread of new infectious diseases has been promoted via active exchanges following changes to the environmental ecosystem and globalisation (Meng, 2015). Experts predict that a new epidemic is possible and represents a global threat (Jung et al, 2019). Representative cases of newly emerging infectious diseases in South Korea include severe acute respiratory syndrome (SARS) in 2003, novel influenza A (H1N1) in 2009 and Middle East respiratory syndrome (MERS) in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the novel influenza A epidemic in May 2009 led to recognition of the need to reinforce response infrastructure for newly emerging infectious diseases, including expansion of the quarantine system and surveillance network, improvement of patient isolation and disease diagnosis/treatment systems, stockpiling of medicines and medical devices, and education and training of medical personnel (Jeong, Park, Wang, & Kim, 2015). It has been predicted that Korea's ability to cope with newly emerging infectious diseases in preparation for a pandemic would be insufficient (Wang, 2014), and when MERS occurred in 2005, it spread rapidly due to insufficient medical systems and resources, and the government's improper response, which engendered fear in medical staff and the public (Jung et al, 2019).…”
Section: Introductionmentioning
confidence: 99%